The Importance of the Islamic Education Philosophy Principles in the 21st-Century Education Context at SMK IT Khoiru Ummah Curup - Putri Adelia (CV Media Inti Teknologi, 2024)
Education has a big impact on people and society. The tenets of Islamic educational philosophy provide a solid basis for guiding a comprehensive and spiritual learning process within the context of Islamic education. Investigating how Islamic educational philosophy can be applied to 21st-century learning at SMK IT Khoiru Ummah Curup is the aim of this project. This study uses a qualitative descriptive approach as its main focus, which is the method employed in this study. This study used triangulation, documentation, interviews, and observation as data gathering methods. The analysis's findings demonstrate that these ideas are still applicable to SMK IT Khoiru Ummah Curup's 21st century curriculum. The findings of this study help SMK IT Khoiru Ummah Curup better grasp the applicability of Islamic educational philosophy's tenets to 21st-century learning. Creating a curriculum and instructional strategies that are more appropriate for the modern Islamic educational setting is one of the practical consequences of the research. It is believed that this study will help educational institutions like SMK IT Khoiru Ummah Curup successfully incorporate Islamic teaching concepts into the 21st-century learning environment. The study's findings demonstrate that Islamic educational philosophy's tenets are still applicable and advantageous in the context of SMK IT Khoiru Ummah Curup's 21st-century curriculum.